Influence of Natural Zeolite and Mineral additive on Bacterial Self-healing Concrete: A Review - J. N. Akhtar; Rizwan Ahmad Khan; Rehan Ahmad Khan; Mohammad Nadeem Akhtar; Jamal K. Nejem (Civil Engineering Journal, 2022)
With time, the development of micro-cracks in concrete is a frequently reported problem in the structures due to the ingress of harmful substances, leading to the degradation of its quality and strength, which ultimately declines the construction. The present work is a review paper based on enhancing the self-healing property of concrete by inducing different bacteria alone or incorporating different mineral additives. It has been seen that various rehabilitated methodologies are in queue to surmount concrete’s weaknesses and to increase its strength and durability. The latest methodology includes using non-pathogenic microbes in concrete as Microbial induced Calcium Carbonate Precipitation (MICCP). The property of precipitating calcium carbonate (CaCO3) crystals by their metabolic activities helps repair the cracks in harsh conditions and improve their strength. Ureolytic bacteria like Bacillus pasteurii/Sporosarcina pasteurii, Bacillus subtilis, Bacillus megaterium, etc., have a specific property by which they can excite urea when integrated with a calcium source and help in sealing the cracks by CaCO3 precipitation. Different studies have observed that specimens having a bacterial concentration of 105-107 cells/ml with Natural Zeolite (NZ) replacement (10%) represents better interaction of the microstructure of concrete because of the formation of calcium silicate hydrate (CSH) gel. Further, the reduction in CH bond with reduced pore space has also been observed. NZ alone enhances micro-structural property, but it shows CaCo3 precipitation and more densification of microstructure under bacterial combination. XRD also confirms an increase in the calcite composition when the bacterial concentration of 105-107 cells/ml is used. The overall properties of standard and high-strength bacterial concrete (105-107 cells/ml) with 10% Natural Zeolite replacement can provide a better option for the future of sustained and strong concrete. Doi: 10.28991/CEJ-2022-08-05-015 Full Text: PDF